Parameters for quantifying bolus retention with high-resolution impedance manometry - Lin, Zhiyue (2014)
BACKGROUND: This study aimed to develop a methodology for quantifying esophageal bolus retention using a high-resolution esophageal impedance topography (EIT) technique. METHODS: The ability of impedance to quantify bolus retention was validated by comparison with concurrent fluoroscopic imaging (barium bolus) in 10 healthy subjects. High-resolution impedance manometry (HRIM) studies without fluoroscopy were performed in another 15 healthy subjects to define normal values using saline. HRIM data from each subject were analyzed using a MATLAB program customized for calculating the esophageal impedance integral (EII) prior to the contraction wave-front as EII1 and after the contraction as EII2, and presented as a ratio of EII2/EII1, which was compared to the percent of barium areas retained in the esophagus on fluoroscopy determined by a blinded reviewer. KEY RESULTS: In 93% (37/40) of barium swallows, the results from the EIT method were in agreement with fluoroscopy results with one of three patterns: 1) 25 normal bolus transit, 2) 8 bolus stasis, and 3) 4 retrograde escape or reflux. Three swallows (8%) had slight retention identified by EIT, but no retention detected by fluoroscopy. The correlation between percent of bolus retained in the esophagus detected by fluoroscopy and percent of bolus retention (EII2/EII1) after swallows with EIT method was r=0.96 (p<0.001) in supine and r=0.69 (p<0.001) in upright position. CONCLUSIONS & INFERENCES: The EII ratio (EII2/EII1) is a surrogate for the fraction of retained bolus after a swallow and this metric may be useful in better defining esophageal function.